Integrons in the development of antimicrobial resistance: critical review and perspectives - Bhat, Basharat Ahmad; Mir, Rakeeb Ahmad; Qadri, Hafsa; Dhiman, Rohan; Almilaibary, Abdullah; Alkhanani, Mustfa; Mir, Manzoor Ahmad (Frontiers in Microbiology, 2023)
Antibiotic resistance development and pathogen cross-dissemination are both considered essential risks to human health on a worldwide scale. Antimicrobial resistance genes (AMRs) are acquired, expressed, disseminated, and traded mainly through integrons, the key players capable of transferring genes from bacterial chromosomes to plasmids and their integration by integrase to the target pathogenic host. Moreover, integrons play a central role in disseminating and assembling genes connected with antibiotic resistance in pathogenic and commensal bacterial species. They exhibit a large and concealed diversity in the natural environment, raising concerns about their potential for comprehensive application in bacterial adaptation. They should be viewed as a dangerous pool of resistance determinants from the “One Health approach.” Among the three documented classes of integrons reported viz., class-1, 2, and 3, class 1 has been found frequently associated with AMRs in humans and is a critical genetic element to serve as a target for therapeutics to AMRs through gene silencing or combinatorial therapies. The direct method of screening gene cassettes linked to pathogenesis and resistance harbored by integrons is a novel way to assess human health. In the last decade, they have witnessed surveying the integron-associated gene cassettes associated with increased drug tolerance and rising pathogenicity of human pathogenic microbes. Consequently, we aimed to unravel the structure and functions of integrons and their integration mechanism by understanding horizontal gene transfer from one trophic group to another. Many updates for the gene cassettes harbored by integrons related to resistance and pathogenicity are extensively explored. Additionally, an updated account of the assessment of AMRs and prevailing antibiotic resistance by integrons in humans is grossly detailed—lastly, the estimation of AMR dissemination by employing integrons as potential biomarkers are also highlighted. The current review on integrons will pave the way to clinical understanding for devising a roadmap solution to AMR and pathogenicity. Graphical Abstract The graphical abstract displays how integron-aided AMRs to humans: Transposons capture integron gene cassettes to yield high mobility integrons that target res sites of plasmids. These plasmids, in turn, promote the mobility of acquired integrons into diverse bacterial species. The acquisitions of resistant genes are transferred to humans through horizontal gene transfer.